2022
DOI: 10.1155/2022/7503553
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Autophagy in Microglia Aggravates Repeated Social Defeat Stress-Induced Social Avoidance

Abstract: Major depressive disorder (MDD) is associated with repeated exposure to environmental stress. Autophagy is activated under various stress conditions that are associated with several diseases in the brain. This study was aimed at elucidating the autophagy signaling changes in the prefrontal cortex (PFC) under repeated social defeat (RSD) to investigate the involvement of microglial autophagy in RSD-induced behavioral changes. We found that RSD stress, an animal model of MDD, significantly induced initial autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…The SPT was performed as previously described [ 20 ]. It employed a two-bottle, free-choice sucrose consumption paradigm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPT was performed as previously described [ 20 ]. It employed a two-bottle, free-choice sucrose consumption paradigm.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed using a standard protocol [ 20 , 21 ]. In brief, mice were anesthetized with an i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the understanding of the existence of plasticity, stressful events can evoke adaptive coping mechanisms that occur both in the central nervous system (CNS) and in the peripheral nervous system and are able to generate resilience ( Russo et al, 2012 ; Pfau and Russo, 2015 ). Recently, a research group demonstrated that synaptic plasticity-related molecules in the hippocampus are associated with susceptibility to social defeat stress in mice ( Lee et al, 2021 ) and another group revealed the involvement of autophagy signaling proteins; however, these proteins are increased in microglia cells of the prefrontal cortex of susceptible and resilient male mice ( Sakai et al, 2022 ). In the hippocampus, autophagy also was reported to be associated with chronic unpredictable mild stress ( Xiao et al, 2018 ).…”
Section: Depression and Resilience To Stress: Synaptic Plasticitymentioning
confidence: 99%
“…Li showed that a miR-223 inhibitor induced autophagosome and autolysosome production in microglial BV2 cells via the ATG16L1-LC3 pathway in response to LPS stimulation (Li et al, 2019). Sakai found that defective autophagy in microglia of the prefrontal cortex exacerbated repeated social defeat (RSD)-induced social avoidance (Sakai et al, 2022). Unlike canonical autophagy, noncanonical pathways do not require the hierarchical contribution of all ATG proteins.…”
Section: Mechanism Of Microglial Autophagymentioning
confidence: 99%